INTERNATIONAL EXPERIENCES OF IMPLEMENTATION OF AUTOMOTIVE CLUSTERS - D. Shlyakhov (Вестник университета, 2016)
The article describes the experience of creating the automotive cluster, which may contribute to the improvement of the structure of the regional economy and ensure its transition to an innovative path of development. Effective strategy development can increase the investment interest in the domestic automotive industry, and to increase the percentage of localization of production at our automobile factories.